PERANAN ORANG TUA DALAM PERKEMBANGAN IMAN ANAK: KELUARGA SEBAGAI PUSAT PENDIDIKAN PERTAMA MENURUT ULANGAN 6:7 - Pasaribu, George Rudi Hartono (JURNAL TABGHA, 2024)
Family education is an essential part of the formation and development of the faith of the child, and the family is a wonderful work of God for mankind as well as an important platform for shaping a better life for the family in the future. All this demands a serious and responsible role from parents. Parents should prioritize the implementation of all the commandments of God in His laws in the family, namely to make the family the educational center for building the spiritual intelligence of the child from an early age, which includes the teachings of compassion, discipline, appreciation, spiritual growth. The writer used literary descriptive methods to obtain data to study Deuteronomy 6:7 as a whole. In this study the author finds that the family is the first educational centre that plays a role in the development of the faith of the child, with the principles found in Deuteronomy 6:7, the modern family can apply the special command given to the Israelites about how to live family life.